2020
DOI: 10.1101/2020.01.15.907626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Telomerase Expression is under Direct Transcriptional Control of the Telomere-binding-factor TRF2

Abstract: Tight regulatory mechanisms to maintain repression of human Telomerase (hTERT), the sole protein that synthesizes telomeres, is crucial for normal adult somatic cells. In contrast, enhanced telomerase activity and resulting pathological maintenance of telomeres, is widely understood as causal in >90% of human cancers. These implicate underlying mechanisms connecting hTERT regulation and telomeres, possibly through telomeric proteins, that remain unclear. In light of of recent work by us and others showing non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…More recent work, on the other hand, suggested that hTERT regulation is under direct transcriptional control of TRF2 (118). Here, TRF2 presence on the hTERT promoter was independent of telomeres (i.e.…”
Section: Role Of Telomere-associated Factors In Pluripotency or "Stemness" And Diseasementioning
confidence: 60%
See 2 more Smart Citations
“…More recent work, on the other hand, suggested that hTERT regulation is under direct transcriptional control of TRF2 (118). Here, TRF2 presence on the hTERT promoter was independent of telomeres (i.e.…”
Section: Role Of Telomere-associated Factors In Pluripotency or "Stemness" And Diseasementioning
confidence: 60%
“…there was involvement of extra-telomeric TRF2). This was also clear from TRF2 occupancy at the exogenously inserted hTERT promoter ;46 Mb away from telomeres (118)-where looping due to physical proximity like the 5p telomere end was unlikely. Together, these leads suggest the involvement of the TSP model discussed above in hTERT regulation, where the presence of extra-telomeric TRF2 on the hTERT promoter is of interest and depends on how much TRF2 is free or sequestered at the telomere ends.…”
Section: Role Of Telomere-associated Factors In Pluripotency or "Stemness" And Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…The TRF2 GAR domain has been shown to bind the 4-way junctions formed at T-loops and restrict promiscuous telomere recombination 96 . TRF2 was also shown to inhibit telomerase expression in normal cells via its interaction with G4 structures in the TERT promoter, although it is not clear if the GAR domain was required for this activity 97 . TRF2 may interact with G4 DNA through domains other than GAR, and the GAR domain is known to have functions in addition to TERRA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NM23-H2-TRF2 interaction suggests potential co-regulation through association with G-quadruplexes. An example of this is the regulation of hTERT, where independently both NM23-H2 [ 12 ] and TRF2 [ 96 ] have been observed to control hTERT by binding to promoter G-quadruplexes.…”
Section: Emerging Aspects and Future Questionsmentioning
confidence: 99%